THE APPLICATION OF ROLE PLAYING LEARNING MODEL TO IMPROVE RESPONSIBILITY AND LEARNING ACHIEVEMENTS (Study at Social Science Subject In VIII Grade Students of Junior High School 1 Rejang Lebong) - Aswan Milaga; Alexon Alexon (DIADIK, 2019)
This research was aimed to describe, first the application of the role playing learning model that can improve the students' responsibility, the second role playing learning models can improve the students' social studies learning achievements, third the effectiveness of applying the role playing learning model to improve students' social studies learning achievements. This research used a classroom action research design and continued with quasi-experiments. The data collection was done by tests and observation. The subject of this classroom action research was the VIII.C grade students of Junior High School 1 Rejang Lebong. The students in class VIII.D was used as the experimental class and the students in class VIII.B was used as the control class. The results of this research showed that the application of the role playing learning model can improve responsibility and learning achievement of social studies students, and the application of role playing learning models can improve social studies learning achievement at Junior High School 1 Rejang Lebong